Machines, computations, and universality : 7th International Conference, MCU 2015, Famagusta, North Cyprus, September 9-11, 2015, Proceedings /: 7th International Conference, MCU 2015, Famagusta, North Cyprus, September 9-11, 2015, Proceedings. (2015) - Unknown
No abstract available